The Response of Consumption in Russian Households to Economic Shocks - Steven Stillman (Institute for the Study of Labor (IZA), 2001)
This paper examines the extent to which consumption in Russian households responds to exogenous income shocks. During the time period studied in this paper (1994 – 1998), Russia experienced two major economic crises. Both featured extreme movements in the real ruble-dollar exchange rate. The price of oil, which is typically thought to have a strong effect on the Russian economy, was also quite volatile during this time period. This paper exploits these large changes in oil prices and exchange rates, as well as community-level variations in wage and pension arrears, to identify exogenous shocks to household income. Using representative panel data on urban households from the Russian Longitudinal Monitoring Survey, I find that a household which experiences an exogenous shock of 10% of its total income changes both its food and total non-durable expenditure by 7-11%. Most evidence indicates that these shocks are transitory in nature and thus the traditional Life Cycle/Permanent Income Hypothesis model is firmly rejected as describing the behavior of Russian households. Additional results indicate that changes in household savings are negatively related to exogenous income shocks, with this relationship strongest for low wealth households. Only models of consumption which include precautionary savings motives can explain why poorer households both reduce their consumption and increase their savings in response to an exogenous decline in income.
Keywords: D91; O16; D12; P36; 330; Consumption; savings; consumption smoothing; precautionary savings; economic shocks; Russia; Konsumentenverhalten; Verbraucherausgaben; Schock; Konsumtheorie; Schätzung; Russland